2022
DOI: 10.3389/fimmu.2022.913714
|View full text |Cite
|
Sign up to set email alerts
|

Anti-DFS70 antibodies in systemic lupus erythematosus: Prevalence in a large Chinese cohort and an unexpected association with anti-dsDNA antibodies by a long-term follow-up

Abstract: ObjectiveMonospecific autoantibodies to dense fine speckles 70 (DFS70) antigen are purported to aid in excluding systemic autoimmune rheumatic diseases (SARD) such as systemic lupus erythematosus (SLE). However, the non-isolated anti-DFS70 still has a certain prevalence in SLE patients, and the clinical significance remains unclear. We aimed to investigate the prevalence, clinical relevance, and value of long-term monitoring of anti-DFS70 antibodies in SLE patients.MethodsAnti-DFS70 antibodies were measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Those laboratory parameters are considered to be the indicators of the active phase of SLE. These results suggest also a positive association between the presence of anti‐DFS70 and anti‐dsDNA 19 …”
Section: Slementioning
confidence: 63%
See 2 more Smart Citations
“…Those laboratory parameters are considered to be the indicators of the active phase of SLE. These results suggest also a positive association between the presence of anti‐DFS70 and anti‐dsDNA 19 …”
Section: Slementioning
confidence: 63%
“…14,16 The high level of these antibodies in a healthy population suggests that, if they are present in SLE patients, they can have a protective function and promote an enhanced response to SLE treatment. 17,18 Dai et al 19 evinced that the presence of anti-DFS70 autoantibodies in SLE patients is positively correlated with younger age, higher anti-dsDNA level, reduced C3 and C4 concentration, an elevated erythrocyte sedimentation rate (ESR), mucosal ulcers and leukopenia. Those laboratory parameters are considered to be the indicators of the active phase of SLE.…”
Section: Slementioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies on Chinese SLE cohort reported higher anti-DFS70 prevalence [11,21] compared with European [12,13] and American studies [6]. A Japanese study also showed that the prevalence of anti-DFS70 antibodies was generally higher in Japanese SARD patients than in patients in Europe and USA [14].…”
Section: Introductionmentioning
confidence: 89%
“…Recent studies have cast doubt on the performance of anti‐DFS70 antibodies for excluding AARD 16,18–22 . The prevalence of anti‐DFS70 antibodies in AARD varies in different studies 16,23–25 . A meta‐analysis found that in patients with positive ANA test results, the pooled specificity of using anti‐DFS70 antibodies to exclude AARD was 98%, but the pooled sensitivity was only 18% 26 .…”
Section: Introductionmentioning
confidence: 99%